2014
DOI: 10.1086/651678
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Environmental Contamination with USA300 Methicillin-Resistant Staphylococcus aureus and Other Pathogenic Strain Types in Households with S. aureus Skin Infections

Abstract: We found that infecting S. aureus isolates frequently persisted environmentally in households 3 months after skin infection. Presence of pathogenic S. aureus strain type in the environment in a household may represent a persistent reservoir that places household members at risk of future infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…These epidemic strains also are capable of prolonged survival in households. USA300 infection was found in 63% of households at three months where there was an antecedent infection [58]. In a longitudinal study, Miller et al confirmed these earlier studies showing that patients with a S. aureus skin infection were more likely to have a recurrent infection within 6 months in households with environmental MRSA contamination.…”
Section: Staphylococcus Aureus Transmission and Disease Within The Homentioning
confidence: 83%
See 4 more Smart Citations
“…These epidemic strains also are capable of prolonged survival in households. USA300 infection was found in 63% of households at three months where there was an antecedent infection [58]. In a longitudinal study, Miller et al confirmed these earlier studies showing that patients with a S. aureus skin infection were more likely to have a recurrent infection within 6 months in households with environmental MRSA contamination.…”
Section: Staphylococcus Aureus Transmission and Disease Within The Homentioning
confidence: 83%
“…Several studies have highlighted the household’s role as the primary reservoir for S. aureus in the community [24, 25, 41, 4358]. The events that follow a CA-MRSA infection in a household include an increase in: (i) the risk of infections among other household members [26, 44, 45, 4851]; (ii) MRSA colonization among other household members [46, 47, 5257, 59]; and (iii) contamination of environmental surfaces [24, 25, 58].…”
Section: Staphylococcus Aureus Transmission and Disease Within The Homentioning
confidence: 99%
See 3 more Smart Citations